Supporting Africa’s Pastoralist Youth to mobilize and engage in policy dialogues: the Africa Youth Pastoralist Initiative - International Livestock Research Institute (CGIAR System Organization, 2024)
A coverage of the Africa Youth Pastoralist Initiative forum held in June 2024 in Nairobi, Kenya, where the group created a renewed vision, mission and statement.